Basic nutrition and diet therapy : textbook for allied health - Caudal, Maria Lourdes Cruz- (Quezon City, Philippines : C & E Publishing Inc., 2019)
Topics range from the process of digestion and metabolism, to nutrients, nutrition across lifespan, therapeutic diets, malnutrition, and enteral and parenteral nutrition.
Chapter 1. Composition of cells -- Chapter 2. Process of digestion -- Chapter 3. Macronutrients -- Chapter 4. Micronutrients -- Chapter 5. Process of Metabolism -- Chapter 6. Physiologic Value of Food -- Chapter 7. Water and electrolyte Balance -- Chapter 8. Nutritional Assessment -- Chapter 9. Pregnancy Lactation -- Chapter 10. Infancy -- Chapter 11. Childhood -- Chapter 12. Adolescence -- Chapter 13. Adulthood -- Chapter 14. Elderhood -- Chapter 15. Inroduction to therapeutic nutrition -- Chapter 16. Enternal and parenteral nutrition -- Chapter 17. Therapeutic Diets -- References -- Index.
Includes bibliographical references and index.
Keywords: NUTRITION